Escolhas e consequências da ação humana: uma hermenêutica de AP. 6:1-8. - Cortez Filho, Carlos Cabanas de Campos (2018)
This work emphasizes the freedom of choices and consequences of human actions and makes a hermeneutic approach to apocalyptic judgments recorded in the book of revelation written by John, specifically in Revelation 6: 1-8, where there are four characters, commonly known as the four knights of apocalypse, mounted on horses of various colors, as being apparently responsible for the execution of such judgments arising from the opening of the seals by the lamb, in hermeneutics. In the development of this analysis we seek the encounter of the thoughts of some authors of the patristic and contemporary approaching the freedom of human choice as responsible for punishments on humanity. This research intends to analyze the text in question related to others of the Old Testament, the characteristics of the horses and knights present, their colors, ornaments and missions. Concluding that the post-Diluvian divine oracle promises to no longer punish the earth, since the intrinsic evil in the heart of man and the divine directives of his choices guide the destruction of mankind.